2009
DOI: 10.1007/s11746-009-1403-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Dairy Phospholipids by 31P NMR

Abstract: 31 P NMR analysis of samples prepared in a sodium cholate detergent system was assessed as a method for the quantitative measurement of dairy phospholipids. Major phospholipid (PL) classes measured included: phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylserine (PS), phosphatidylinositol (PI), sphingomyelin (SM) and dihydrosphingomyelin (DHSM). The 31 P NMR method was validated by comparison with a quantitative two-dimensional thin-layer chromatography (2D-TLC) technique. The 2D-TLC syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 20 publications
5
70
0
1
Order By: Relevance
“…Previous 31 P NMR characterisation of PLs conducted mainly on cow milk (Andreotti et al, 2006;MacKenzie et al, 2009;Murgia et al, 2003) can be directly compared with our data (Table 4). The use of the monophasic solvent system trimethylamine/dimethyl-formamide/guanidinium hydrochloride resulted in an underestimation of PE quantification due to the formation of different adducts (Andreotti et al, 2006;Murgia et al, 2003) when compared to a protocol using a detergent system at pH 7.1 (MacKenzie et al, 2009), or to our biphasic system at pH 7.7, which showed the best resolution of the PE peak; in addition, the PS peak was not well-resolved and was underestimated that was solved also by the two latter protocols.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous 31 P NMR characterisation of PLs conducted mainly on cow milk (Andreotti et al, 2006;MacKenzie et al, 2009;Murgia et al, 2003) can be directly compared with our data (Table 4). The use of the monophasic solvent system trimethylamine/dimethyl-formamide/guanidinium hydrochloride resulted in an underestimation of PE quantification due to the formation of different adducts (Andreotti et al, 2006;Murgia et al, 2003) when compared to a protocol using a detergent system at pH 7.1 (MacKenzie et al, 2009), or to our biphasic system at pH 7.7, which showed the best resolution of the PE peak; in addition, the PS peak was not well-resolved and was underestimated that was solved also by the two latter protocols.…”
Section: Discussionmentioning
confidence: 57%
“…The use of the monophasic solvent system trimethylamine/dimethyl-formamide/guanidinium hydrochloride resulted in an underestimation of PE quantification due to the formation of different adducts (Andreotti et al, 2006;Murgia et al, 2003) when compared to a protocol using a detergent system at pH 7.1 (MacKenzie et al, 2009), or to our biphasic system at pH 7.7, which showed the best resolution of the PE peak; in addition, the PS peak was not well-resolved and was underestimated that was solved also by the two latter protocols. Ether lipids (ethanolamine plasmalogen and alkyl-acyl-phosphatidylcholine) were not detected in two published works (Andreotti et al, 2006;MacKenzie et al, 2009), but an EPLAS level close to the one we found was reported by Murgia et al in spite of their very different protocol and of their weak resolution of this peak (Murgia et al, 2003). By comparison to these three published protocols, our current approach provides better resolution (well separated and narrower peaks, especially for PI), probably due to the setting of an optimal temperature (25°C for cow, camel and human milk, and 5°C for mare milk); this might also explain why our cow milk PI level is lower than the published values.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lipids were extracted using the Bligh and Dyer method (39). The NMR analysis was performed as described (40). Briefly, the lipid extracts were suspended into 500 l of the cholate detergent system through vortexing and dispersion in a sonicating bath at 60°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Reported techniques to determine PS in dairy products following a lipid extraction include thin layer chromatography (TLC) [12], 31 P-Nuclear Magnetic Resonance (NMR) spectroscopy [13] and high-performance liquid chromatography coupled with an evaporative light scattering detector (HPLC-ELSD) [14]. While TLC is more suitable for qualitative and semi-quantitative purposes [15], 31 P-NMR is unsuitable for routine analysis due to its high cost.…”
Section: Introductionmentioning
confidence: 99%